Instrumentation of an ergometer paddle to be integrated with an instrumented footrest and foot-strap to assess upper and lower-body force contributions during paddling - Hong, Mervyn Jun (Nanyang Technological University, 2020)
Sprint kayaking is an Olympic sport that demands a high level of technical skill and physical capability. Athletes race in a closed-deck carbon composite kayak and use a double-sided wing paddle to propel the boat down a straight racing lane over 200m, 500m or 1000m in the shortest time possible. Athletes must be able to effectively transfer internal forces generated by their muscles from the upper and lower body to maintain a high average velocity throughout the race to be successful. Most research in kayaking has focused on the force contributions from the upper and lower body while paddling on an ergometer or boat as indicators of performance. There has been minimal research that focused on the force contributions from the lower body to kayaking performance. Understanding the force contributions from both the upper- and lower body to kayaking performance would provide coaches, researchers and athletes a more holistic understanding of full body paddling mechanics. Predecessors of this project instrumented a footrest and footstrap that is installed on a kayak ergometer to study the respective push and pull forces generated by the lower body during training. Bilateral push and pull forces are displayed through a software for immediate feedback and technique correction when necessary. This project aims to instrument the paddle of a kayak ergometer to obtain upper body force contributions and which will be synchronised with the lower body force data to provide a holistic analysis of the upper and lower body force contributions when a kayaker uses an ergometer for training.